COVID-19 Vaccines: A Literature Review - de Sa Vilela Filho, Alexander; Menegale Bianchetti, Breno; Malard Peixer, Carolina; Santos Cordón, Matheus; de Oliveira Felipe Rocha, Mayara; Cardoso Ribeiro Vasconcelos, Vinicius (Seven Editora, 2023)
Introduction: In 2019, the SARS-Cov-2 virus emerged in Wuhan province, China, causing the pandemic of COVID-19 (R. MOJICA-CRESPO et al, 2020). In Brazil, the first confirmed case of COVID-19 was recorded on February 26, 2020 (MINISTÉRIO DA SAÚDE, 2020). In an effort to reduce the spread of this virus and end the pandemic, scientists around the world have worked to develop efficient and safe vaccines in record time to combat the pathogen. At the time of writing, 104 vaccines are under development, 8 approved by the World Health Organization (WHO, 2020) (KNOLL M D ET AL, 2020) and 4 approved by Brazil's    National   Health    Surveillance   Agency (ANVISA, 2020). Objective:    To     determine    the    difference    in susceptibility to develop the severe form of the disease in people who had Covid and were vaccinated, compared to those who were not vaccinated in Brazil. Material and Methods: The review was based on articles published in national and international databases, such as Scielo and PubMed, as well as websites of the World Health Organization, Pan American Health Organization, Ministry of Health, National Health Surveillance Agency, among others. Final Considerations: The present literature review concluded that the four vaccines approved by ANVISA have proven efficacy in fighting the development, but mainly in aggravating the clinical picture of the new coronavirus disease, with certain exceptions of some vaccines in pregnant women and children due to the lack of data collected from these two specific groups. Thus, besides all the biosafety protocols recommended by the health agencies during the pandemic scenario, it can be seen that vaccination was responsible for controlling the number of new cases of the disease in Brazil and that it brought significant improvement in the lives of those infected by the new coronavirus, avoiding the worsening of the clinical picture and reducing the mortality rate. DOI: 10.56238/pacfdnsv1-003